PROFIL PENYIMPANAN OBAT DI UNIT PELAKSANAAN TEKNIS DAERAH (UPTD) PENGELOLAAN OBAT DINAS KESEHATAN KOTA MAKASSAR - Andi Muflihunna; Iskandar Zulkarnain; Hasni. A Hasni. A (As-Syifaa Jurnal Farmasi, 2022)
The pharmacy storage facility is responsible for maintaining the supply of medicines to avoid damage and expiration as well as maintaining the quality of medicines stored in the facility. As a result, this investigation concerning the profile of drug storage at the UPTD of Drug Management of Makassar City Health Office, is necessary. The study aimed to determine the drug storage profile in the UPTD of Makassar City Health Office. The present study employs a descriptive qualitative approach. Direct observation, in- depth interviews, and document analysis were used to collect data. The informants for this study were the head of the UPTD and pharmaceutical personnel at the UPTD of Drug Management of Makassar City Health Office. The aspects examined and percentages obtained were facilities and spatial arrangements (82.3 percent), drug stock preparation (81.8 percent), stock card recording (87.5 percent), and checking conditions and drug storage (87.5 percent). The results showed that all areas examined fell into the very good category and were consistent with the guidelines of Health Ministry of the Republic of Indonesia 2002, Regulation numbers 72, 73, 74 of 2016, and Technical Guidelines of 2019. Even though drug storage activities are not directly related to patients, ignoring them will result in significant losses for the Health Office